Toward a Dielectric Elastomer Resonator Driven Flapping Wing Micro Air Vehicle - Cao, Chongjing; Burgess, Stuart; Conn, Andrew T. (Frontiers in Robotics and AI, 2019)
In the last two decades, insect-inspired flapping wing micro air vehicles (MAVs) have attracted great attention for their potential for highly agile flight. Insects flap their wings at the resonant frequencies of their flapping mechanisms. Resonant actuation is highly advantageous as it amplifies the flapping amplitude and reduces the inertial power demand. Emerging soft actuators such as dielectric elastomer actuators (DEAs) have large actuation strains and thanks to their inherent elasticity, DEAs have been shown a promising candidate for resonant actuation. In this work a double cone DEA configuration is presented, a mathematic model is developed to characterize its quasi-static and dynamic performance. We compare the high frequency performance of two most common dielectric elastomers: silicone elastomer and polyacrylate tape VHB. The mechanical power output of the DEA is experimentally analyzed as a DEA-mass oscillator. A flapping wing mechanism actuated by this elastic actuator and this design is able to provide a peak flapping amplitude of 63° at the frequency of 18 Hz, which is the highest reported flapping performance of a DEA flapping mechanism. While not yet sufficient for hovering flight, the mass-specific power density of the DEA was found to be 100 W/kg at resonance, which demonstrates the viability of this technology. Limiting factors in the current transmission mechanism, such as the transient variability of speed ratio are analyzed towards DEA-driven MAVs.